The iridoid glucoside secologanin is derived from the novel triose phosphate/pyruvate pathway in a Catharanthus roseus cell culture - Contina, A.; van der Heijdena, R.; Lefeberb, A.W.M.; Verpoorte, R.
Secologanin is the iridoid building block of the majority of the terpenoid indole alkaloids. In the biosynthesis of secologanin, mevalonate was considered to be the exclusive precursor of isopentenyl diphosphate. After [1-13C]glucose feeding to a cell culture of Catharanthus roseus, its incorporation into secologanin was studied by 13C NMR spectroscopy. The data showed that the novel triose phosphate/pyruvate and not the mevalonate pathway was the major route for the biosynthesis of secologanin
Keywords: SECOLOGANIN; IRIDOID; ALKALOID; BIOSYNTHESIS; ISOPENTENYL DIPHOSPHATE; 1-DEOXY-D-XYLULOSE